A PI Consensus-Based Second Control for P/V Droop-Controlled Converters in Low-Voltage Resistive Network - Zeng, Yukai; Chen, Xia; Sun, Shumin; Zhou, Guangqi; Cheng, Yan; Wang, Shibai (2023 IEEE 7th Conference on Energy Internet and Energy System Integration (EI2), 2023)
Droop control is widely used to achieve desired power sharing among distributed generations (DGs). For low-voltage resistive network, P/V droop control is preferred rather than the conventional droop. However, P/V droop also suffers from inaccurate active power allocation and deviation of voltage and frequency from rated values induced by inequal line impedance and its inherent defects. A PI-consensus based secondary controller is hereby proposed for the P/V droop control to address these problems. With the effect of PI-consensus algorithm, the deviations of voltage and frequency are minimized, and the active power of DGs reach a consensus, achieving desired power allocation. Simulations are conducted to verify the effectiveness and the robustness of the proposed second control in an islanded low-voltage resistive power system. Besides, an experiment is carried out to further validate its efficacy.